Review Of Islam Law On The Impact Of Thrift Selling Of Goods In Gorontalo City - Salim Alidrus; Nur Mohammad Kasim; Waode Mustika (Estudiante Law Journal, 2023)
The purpose of this study is that this research discusses the review of Islamic law on the impact of buying and selling thrift goods in Gorontalo City . As for the objectives of this research are: to find out how the review of Islamic law on the impact of buying and selling thrift goods in Gorontalo City. This study uses empirical legal research methods. Empirical legal study itself is a study that views law as a reality, including social reality, cultural reality, and empirical studies of the world. This research took place at the Saturday and Sunday Markets in Gorontalo City. The results obtained from this study are that in Islamic law the practice of selling is not in accordance with one of the pillars and conditions of the contract, namely Ma'qud alaih (object), because the goods are not clearly specified. Sellers and buyers do not know clearly the quality of goods with certainty or gharar. Therefore, this thrift sale and purchase is included in the ghajr sahih fasid contract because one of the pillars is not fulfilled and ghair shahih , a vanity contract because it is not clearly specified so that it does not have a legal impact.